The global future of English studies - English, James F (Wiley-Blackwell/John Wiley & Sons, 2012)
Includes bibliographical references and index; Part 1. The future of English enrollments: massification and global demand: Beyond crisis -- Let's do the numbers -- Not a bust but a boom -- Part 2. The future of English professors: efficiency versus prestige in the age of global rankings: The economics of massification -- Doing more with less -- Demand for the doctorate -- Credentials fever -- Part 3. The future of the English curriculum: literary studies in its global aspect: The end of the discipline as we know it -- Language versus literature-- Manifesto